Global Liquidity and Drivers of Cross-Border Bank Flows - Cerutti, Eugenio (IMF Working Papers; Working Paper, 2014)
This paper provides a definition of global liquidity consistent with its meaning as the 'ease of financing' in international financial markets. Using a longer time series and broader sample of countries than in previous studies, it identifies global factors driving cross-border bank flows, alongside country-specific factors. It confirms the explanatory power of US financial conditions, with flows decreasing in market volatility (VIX) and term premia, and increasing in bank leverage, growth in domestic credit and M2. A new finding is that similar variables for other systemic countries - the UK and the Euro Area - are also important, sometimes even more so, consistent with the dominant role of European banks in cross-border banking. Furthermore, recipient country characteristics are found to affect not only the level of country-specific flows, but also the cyclical impact of global liquidity, with sensitivities of flows to banks decreasing with stronger macroeconomic frameworks and better bank regulation, but less so for flows to non-financial firms.